A Stylistic Analysis of Diverse Linguistic Features in Maupassant’s The Piece of String - Mortaza, Ali; Mohsin, Liaqat Ali; Afzal, Muhammad Imran (Pakistan Journal of Humanities and Social Sciences, 2023)
This article offers a comprehensive stylistic analysis of Maupassant’s renowned short story, The Piece of String including imagery, alliteration, simile and anaphora, using the theoretical perspective of Wales, Nikolyukina, Kemertelidze and Manjavidze. Employing a third-person omniscient narrative voice, Maupassant establishes a sense of intimacy with the characters, delving into their inner thoughts and emotions. Rich and evocative imagery further enhances the story’s vivid portrayal of the Normandy countryside and its inhabitants. Noteworthy is the skillful use of symbolism, with the piece of string serving as a powerful metaphor for the fragility of one’s reputation, susceptible to ruin through the dissemination of rumors. Through repetition, anaphora and suspenseful narrative elements, the author effectively sustains readers’ engagement. This scholarly pursuit constitutes a commendable addition to the realm of literary criticism, enriching the comprehension of Maupassant’s literary finesse, while simultaneously accentuating the import of stylistic exploration in deciphering the strata of meaning enshrined within timeless literary creations.